Prediction of Addiction Potential on the Basis of Aggression and Assertiveness in University Students - Mehrdad Hajihasani; Abdoolah Shafiabadi; Fahmideh Pirsaghi; Mehrab Bashirpour (Drug Control Headquarters, Research and Education Office, 2012)
Introduction: The aim of present research was the prediction of addiction potential on the basis of aggression and assertiveness in Allameh Tabbatabaei girl students. Method: The research method was correlational design and population of research was girl students of Allameh Tabatabaei university. By available sampling 150 girls were selected and Ahvaz Aggression Questionnaire, Gambril & Rigy Assertiveness questionnaire and Zargari Addiction Potential Questionnaire administered among selected sample. Findings: the results of the Pearson correlation showed that the relationship between aggression, assertiveness, and addiction potential was significant. Also, the results of multivariate regression analysis showed that aggression, assertiveness and depression can predict the Addiction Potential. Conclusion: Addiction potential can be predicted by aggression and assertiveness.